PLANNING IMPLEMENTATION AND ORGANIZATION OF PROJECT ACTIVITIES CASE STUDY OF HONEY BRANDY : DOI: 10.5937/etp2402079K - Kuburović, Nina; Ostojić, Bojana; Ilić, Biljana; Čabarkapa, Obrad (Ekonomija - teorija i praksa, 2024)
The paper explores the possibility of the successful implementation and implementation of project management in all spheres of business, especially the application of project management in the process of introducing new products into the production process, which enables the realization of smaller but also more complex projects, which is one of the focuses of the work. The goal of the research deals with the practical application of all known methods and techniques, which the project management has developed during its existence, on the example of the development of a new product in the alcoholic beverages industry - honey brandy by placing that product on the market, with a detailed analysis of the success of the project, analysis of marketing and business plan of this venture.